Patterns of engagement with inflammatory bowel disease online support groups: comparing posters and lurkers - Coulson, Neil S. (Wolters Kluwer, 2015)
Little is known about the varying patterns of member engagement within inflammatory bowel disease online support groups. The aim of the study was, therefore, to compare posters and lurkers (i.e., those who read messages but choose not to post) in terms of engagement and motives for accessing online groups as well as to explore reasons why lurkers do not make an active contribution through posting messages. The findings revealed that those who posted messages visited groups more often and spent longer periods of time accessing them. However, there was no difference between posters and lurkers in terms of length of time as a group member. Furthermore, posters were more inclined to access online support groups to both seek and provide emotional, informational, and experiential support. Finally, four main reasons were described by lurkers for not posting messages and these focused on personal factors, illness severity, being helpful, and new member. For those healthcare professionals or patient volunteers who are involved in supporting inflammatory bowel disease online support groups, there are a number of practical strategies arising from these results which can be implemented to help integrate and encourage active participation by all members.